EFFECT OF COOKING METHODS ON PROXIMATE COMPOSITION OF ROHUAND CROAKER'SSTEAKS - KAR, S.; CHOWDURY, S.; DORA, K. C.; NATH, S.; SINHA, K.; Pati, K. (Journal of the Inland Fisheries Society of India, 2021)
The effect of six different cooking methods (deep frying at 130 oC, 150 oC and180 oC for 15, 7 and 4.5 min respectively, microwave oven (2450 MHz) for 2.5 mins, boiling and steam-cooking) on proximate composition and energy value of Rohuand Croaker steaks were determined. Significant increase (p